ESTIMATION OF GENETIC PARAMETERS FOR POSTWEANING GROWTH TRAITS IN CROSSBRED ANGUS X ZEBU CATTLE - Vasconcelos Silva, Josineudson Augusto de [UNESP]; Maiorano, Amanda Marchi [UNESP]; Bernardo Junior, Flavio Finati [UNESP]; Martins, Giovana Vellasco [UNESP]; Novaes, Lucas Coimbra [UNESP]; Marques da Silva, Daiane Cristina [UNESP]; Curi, Rogerio Abdallah [UNESP] (Inst Zootecnia, 2015)
The objective of this study was to verify the effect of individual heterozygosity on weights at 365 (W365) and 550 (W550) days of age, and to estimate the heritability of these traits and the breeding values of animals of different breed compositions involving Angus and Zebu breeds in order to evaluate the possible use of these traits as selection criteria in crossbreeding and genetic improvement programs. Records from 5,629 crossbred Angus x Zebu animals born between 1995 and 2004 were used. Univariate and bivariate analyses of the traits were performed using an animal model and Bayesian inference. The effects included in the model were contemporary group, individual heterozygosis, age of animal at recording, and random direct genetic effect of the animal and residual. The size of the chain requested, as well as the burn-in period and thinning interval, was sufficient to obtain convergence of the posterior estimates of the genetic parameters. The heritability estimates obtained in univariate and bivariate analysis were 0.38 and 0.30 for W365 and 0.32 and 0.30 for W550, respectively. The genetic correlation between traits was 0.98. Comparison of the rank of the 10 best sires based on the breeding values for W365 and W550 showed a small difference between the traits studied. The effect of heterozygosity has importance for crossings and for obtaining higher postweaning weights, indicating that the use of animals with maximum individual heterozygosity is advantageous. W365 and W550 were found to be appropriate selection criteria and should be included in breeding programs of crossbred Angus x Zebu cattle.
Keywords: growth traits; heterozygosity; breeding value